Eastern Medieval Architecture - Ousterhout, Robert G.
1 online resource (810 pages)
Keywords: The rich and diverse architectural traditions of the Eastern Mediterranean and adjacent regions are the subject of this book, including the social and cultural developments of the Byzantine Empire, the Caucasus, the Balkans, and Russia, as well as parallel developments in Crusader and early Islamic architecture.